7(2x-10)=-42

Simple and best practice solution for 7(2x-10)=-42 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(2x-10)=-42 equation:



7(2x-10)=-42
We move all terms to the left:
7(2x-10)-(-42)=0
We add all the numbers together, and all the variables
7(2x-10)+42=0
We multiply parentheses
14x-70+42=0
We add all the numbers together, and all the variables
14x-28=0
We move all terms containing x to the left, all other terms to the right
14x=28
x=28/14
x=2

You can always share this solution

See similar equations:

| 0.04x+0.11(x+8000)=2230 | | 3x-1+2x+6+x=180 | | Y=|x|-11 | | 7-7r=-3-8r | | 7w+4=20 | | -272=d?870 | | 2+6f=9+7f | | 2^0+2^1-2x=9×2^-1-x | | 7w-3=21 | | 2x+8x=4x | | -5p+8=-4-9p | | 5^2v=25 | | -7(x+2)=x-8+2(3x+2) | | 2g=-5+3g | | 15d+20=110 | | -9u=-8u+7 | | x-25=18;= | | 15j=2+14 | | 4p=2p-8 | | 21=z?53 | | 50=z+-4 | | E^-x=245 | | d+87=-8 | | 1.5t^2+4.9t+2=0 | | 4(-8x-12)=-26-32x | | -3x+7-6(x-1)=-(2x-4)-6x+6 | | b^2+5=17 | | z?-41=54 | | 4u-36=6(u-5) | | d?698=-271 | | -216=-6(1-5r) | | x-4-15=10 |

Equations solver categories